Methodology in private law theory between new private law and Rechtsdogmatik - Kuntz, Thilo 1977-; Miller, Paul B. 1977- (Oxford University Press, 2024)
'Methodology in Private Law Theory' memorializes a first-of-its-kind dialogue between leading lights in German and American private law theory.
This edition also issued in print: 2024. - Includes bibliographical references and index. - Description based on online resource and publisher information; title from PDF title page (viewed on December 16, 2023)
Keywords: Civil law / Germany; Civil law / United States; Civil law / Philosophy; Law; Laws of specific jurisdictions & specific areas of law